2021
DOI: 10.1136/neurintsurg-2021-017940
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast head CT alone for thrombectomy in acute ischemic stroke: analysis of the ANGEL-ACT registry

Abstract: BackgroudThe goal of this study was to determine if the choice of imaging paradigm performed in the emergency department influences the procedural or clinical outcomes after mechanical thrombectomy (MT).MethodsThis is a retrospective comparative outcome study which was conducted from the ANGEL-ACT registry. Comparisons were made between baseline characteristics and clinical outcomes of patients with acute ischemic stroke undergoing MT with non-contrast head computed tomography (NCHCT) alone versus patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…So far, even though AIS diagnosis (such as magnetic resonance imaging and computed tomography) has made great progress, the exploration of potential biomarkers to reflect the disease risk of AIS is still imperative (Ren et al 2022;Yang et al 2022). Previous studies have reported that ITIH4 is dysregulated in cerebral-cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…So far, even though AIS diagnosis (such as magnetic resonance imaging and computed tomography) has made great progress, the exploration of potential biomarkers to reflect the disease risk of AIS is still imperative (Ren et al 2022;Yang et al 2022). Previous studies have reported that ITIH4 is dysregulated in cerebral-cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%